Analisis Tingkat Kepuasan Pengguna Terhadap Bangunan Green Terminal Joyoboyo - Muhamad, Achmad Zein Bin; Alrizal, Fahmi Firdaus (Institut Teknologi Adhi Tama Surabaya, 2023)
The green terminal concept in addressing quality expectations and user satisfaction is very important in the development industry in construction, facilities and energy use in buildings. This research aims to identify problems and also uses literature study by determining variables and validating them by users, then distributing questionnaires. Testing the validity and reliability of the questionnaire was carried out using the SPSS application and also Cronbach's alpha testing. If the validity test of the questionnaire is invalid, then it is rewritten, and if the validity test of the questionnaire is valid then it is continued using the IPA method to determine the level of user expectations and satisfaction in the Joyoboyo terminal building. The results of the physical condition variable have an average of 99%, the facility variable in the building has an average of 100%, the problem variable around the building is 95%, the system factor variable in the building is 98%, the social environment variable in the building is 96% and the location factor variable in the building 98%. At the Joyoboyo terminal, the manager needs to pay attention to the air condition inside the building. In terms of service quality, it is quite good, but from the user's perspective, it is not good because in the building's canteen, waste water disposal is often clogged and makes the air conditions inside uncomfortable and you have to wait for the staff to clean it or the shop owner to clean it. dispose of the waste water itself, therefore it is necessary to increase the quality and user satisfaction value of the Joyoboyo green terminal building.